Hydrogen Peroxide 40% for the Treatment of Seborrheic Keratoses. Issue 2 (February 2021) - Funkhouser, Colton H.; Coerdt, Kathleen M.; Haidari, Wasim; Cardis, Michael A.
Objective: Hydrogen peroxide 40% (HP40) was approved by the US Food and Drug Administration for topical treatment of seborrheic keratosis (SK) in December 2017. This article will review phase II and III clinical trials to assess the drug's efficacy, safety, and clinical application. Data Sources: A systematic literature review was performed using the terms "Eskata AND seborrheic keratosis, " and "hydrogen peroxide AND seborrheic keratosis" in the OVID MEDLINE, PubMed, Cochrane Library, EMBASE, and Web of Science databases. ClinicalTrials.gov was searched to identify ongoing or nonpublished studies. Study Selection and Data Abstraction: Articles written in English between January 2000 and mid-June 2020 discussing phase II and phase III clinical trials were evaluated. Data Synthesis: In 2 phase III clinical trials, 4% and 8% of patients treated with HP40 had a Physician Lesion Assessment score of zero for all 4 SKs, respectively, compared with 0% in both vehicle groups at the primary end point of day 106 ( P < 0.01; P < 0.0001). Relevance to Patient Care and Clinical Practice: HP40, although less effective, has a better safety profile than other treatment options. It should be especially considered for treatment of facial SKs, where it is most efficacious and where other treatment modalities, such as cryotherapy, are more challenging. Conclusions: HP40 is a new, safe alternative treatment for SKs, although it is expensive and only modestly effective, both of which somewhat limit its overall utility. HP40 is a promising topical alternative, particularly for cosmetically sensitive locations, such as the face.